The reclaiming of “Belle Époque” Architecture in Egypt (1989-2010): On the Power of Rhetorics in Heritage-Making - Mercedes Volait (ABE Journal)
The listing as national heritage of “Belle Époque” architecture, a loose category encompassing buildings from the 1850s to the 1950s, forms an intriguing chapter in Egypt’s complex relationship with the past, and moreover with the successive layers of its ancient, medieval, modern and contemporary history. While it would be deemed dissonant heritage by postcolonial theory because of its connections to the colonial era, the legacy of “Belle Époque” has emerged since 1989 as a priceless gem worth preserving. The concern of this essay is to understand how historical objects manage to impose themselves as cultural heritage, when nothing predisposed them to acquire such value. One conclusion is that language and story-telling, or even branding, play a crucial part in the processes of heritage consecration. Another is that processes of social legitimization can be indeed a significant factor. Using a wide range of sources (from the legal framework to the press), the paper reviews the entangled mechanisms that concurred to consecrate “Belle Époque” architecture in Egypt, while acknowledging, through concrete examples, the part played by coincidental or extra-preservation circumstances in the making of heritage.